2014
DOI: 10.1186/1471-2474-15-351
|View full text |Cite
|
Sign up to set email alerts
|

In vivo microstructural analysis of the humeral greater tuberosity in patients with rotator cuff tears using multidetector row computed tomography

Abstract: BackgroundIn arthroscopic surgery, the suture anchor technique has become popular for rotator cuff repair. Preoperative evaluation of the bone microstructure is of utmost importance because, especially in elderly patients, osteoporotic changes may cause anchor pullout, which results in failure of rotator cuff repair. Many groups have reported humeral microstructural analysis; however, most studies were experiments using porcine specimens or human cadavers. In this study, we used multidetector row computed tomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Our study confirmed that 0.5 mm–diameter microfracture was a better choice than 1 mm–diameter microfracture. Through in vivo microstructural analysis of patients with rotator cuff tear, Sakamoto et al 29 found that the average minimum value of trabecular separation of the humeral greater tuberosity was around 0.7 mm located at the posteromedial site. Thus, according to our study and similar studies in the knee, 0.7 mm–diameter microfracture may be the best choice for human rotator cuff surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Our study confirmed that 0.5 mm–diameter microfracture was a better choice than 1 mm–diameter microfracture. Through in vivo microstructural analysis of patients with rotator cuff tear, Sakamoto et al 29 found that the average minimum value of trabecular separation of the humeral greater tuberosity was around 0.7 mm located at the posteromedial site. Thus, according to our study and similar studies in the knee, 0.7 mm–diameter microfracture may be the best choice for human rotator cuff surgery.…”
Section: Discussionmentioning
confidence: 99%
“…
Fig. 2 Trabecular microstructural parameters (reprinted from the literature with permission) [ 18 ]. The black arrow indicates the trabecular thickness (Tb.Th, μm), and the white arrow indicates the trabecular separation (Tb.Sp, μm)
…”
Section: Methodsmentioning
confidence: 99%
“…Baum et al found that microstructure parameters most accurately predict absolute and relative femoral bone quality in cadaver study [ 17 ]. Sakamoto et al reported a microstructural analysis of the humeral greater tuberosity in patients with rotator cuff tears [ 18 ]. Lu et al showed that MDCT might have the potential to characterize the trabecular pattern and distribution of the proximal femur [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…A feature of personalized medicine is evaluating both the variability and unicity of patients in diagnosis and treatment. Research in the orthopedic field is moving towards a better understanding of the musculoskeletal apparatus, bones’ and muscles’ structure and role, applying computational models and innovative imaging techniques [ 41 , 52 , 53 ]. Telemedicine is a promising solution that aims to provide personalized and supervised therapy, breaking down the patient–therapist distance barrier [ 46 ].…”
Section: P5 Medicine In the Management Of Rc Diseasesmentioning
confidence: 99%